Herbert Hart and the semantic sting - Endicott, T (Cambridge University Press, 1998)
Even to disagree, we need to understand each other. If I reject what you say without understanding you, we will only have the illusion of a disagreement. You will be asserting one thing and I will be denying another. Even to disagree, we need some agreement.